Characterization of Fe2O3 thin film on highly oriented pyrolytic graphite by AFM, Ellipsometry and XPS - Kaspar, Pavel; Sobola, Dinara; Dallaev, Rashid; Ramazanov, Shikhgasan; Nebojsa, Alois; Rezaee, Sahar; Grmela, Lubomír (Applied surface science, 2019)
Graphite finds use in a large amount of nanoscale applications, including as a substrate for thin film and nanomaterial deposition. With its excellent properties for usage in nanoscale and given the regularity of structure of highly oriented pyrolytic graphite (HOPG), the possibility of use to acquire more precise and detailed results is high. To this end the basic topographical and structural properties of HOPG and thin Fe2O3 have been explored. Methods used were atomic force microscopy, ellipsometry and x-ray photoelectron spectroscopy. Documentation of the results allows for further examination of HOPG usage possibilities, uncoated or coated with Fe2O3 thin film, as well as a substrate for carbon fiber or nanotube growth in future projects. •Fe2O3 layer is of even thickness over the whole sample due to regularity of HOPG surface.•Fe2O3 forms shortly after exposure to atmospheric oxygen.•Changes in XPS, AFM and Ellipsometry results between clean HOPG and one with Fe2O3 layer clearly visible•Rare artifacts on the surface can cause the appearance of unexpected chemical bonds.•Material provides good starting point for nanomaterial research.